Social Cognitive Theory of Sports at VIP Al-Huda High School - Mudayat Mudayat; M. Mualip (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. By identifying appropriate methods for changing behavior, social cognitive theory can help individuals and organizations achieve their goals and improve outcomes. According to social cognitive theory, individuals learn through a process of observation, imitation, and reinforcement. They observe others performing certain behaviors and then imitate those behaviors based on their perceptions and interpretations of the situation. Reinforcement, both positive and negative, can then influence the likelihood of those behaviors being repeated in the future. Importantly, social cognitive theory also acknowledges the role of personal agency in behavior change. Individuals can make conscious decisions about their behavior and take action to change it. Material and Method. This study is a literature review based on the field of social psychology. It outlines how motivational processes play a significant role in influencing both children and adults. Motivational processes refer to the goals that motivate individuals, their expectations for achieving those goals, and the values that drive them to achieve them. The motivation to learn is closely related to the principle that behavior that has been positively reinforced in the past is more likely to be repeated than behavior that has not been reinforced or has been punished. Result. Motivation plays a crucial role in the learning process. According to motivational theory, motivation is the driving force that creates a level of persistence and enthusiasm in carrying out an activity. This motivation can originate from within the individual (intrinsic motivation) or from external sources (extrinsic motivation). Intrinsic motivation comes from the individual's internal desires and interests, such as a genuine interest in a subject, a desire to learn new skills, or a sense of accomplishment. Extrinsic motivation, on the other hand, comes from external factors such as rewards, praise, or recognition. By understanding and harnessing both types of motivation, learners can maintain their interest and enthusiasm throughout the learning process, leading to greater success and achievement. Conclusion. This sentence refers to the importance of having a good learning facilitator who motivates students to actively participate in the learning process to achieve academic success. In other words, a skilled and effective teacher can be compared to a proficient driver who guides students toward their learning goals by encouraging them to engage with the subject matter actively and thoughtfully. This approach can help students to develop a deeper understanding of the material and to become more invested in their learning, leading to greater academic achievement and personal growth